Right Heart Pressure Increases after Acute Increases in Ambient Particulate Concentration - Rich, David Q.; Freudenberger, Ronald S.; Ohman-Strickland, Pamela; Cho, Yong; Kipen, Howard M. (Environmental health perspectives, 2008)
Objectives: Objectives: We explored the association between acute changes in daily mean pulmonary artery (PA) and right ventricular (RV) pressures and concentrations of ambient fine particulate matter [PM with aerodynamic diameter ≤ 2.5 μm$({\rm PM}_{2.5})$] as an explanation for previous associations between congestive heart failure (HF) hospital admissions and PM. Materials and methods: In the Chronicle Offers Management to Patients with Advanced Signs and Symptoms of Heart Failure (COMPASS-HF) trial, to see whether management of ambulatory HF could be improved by providing continuous right heart pressure monitoring to physicians, the Chronicle Implantable Hemodynamic Monitor (Medtronic, Inc., Minneapolis, MN, USA) continuously measured multiple right heart hemodynamic parameters, heart rate, and activity trends in subjects with moderate/severe HF. Using these trial data, we calculated daily mean pressures, using only those time intervals where the subject was not physically active (n = 5,807 person-days; n = 11 subjects). We then studied the association between mean daily PA/RV pressures and mean ambient${\rm PM}_{2.5}$concentrations on the same day and previous 6 days. Results: Each 11.62-μg/m³ increase in same-day mean${\rm PM}_{2.5}$concentration was associated with small but significant increases in estimated PA diastolic pressure [0.19 mmHg; 95% confidence interval (CI), 0.05-0.33] and RV diastolic pressure (0.23 mmHg; 95% CI, 0.11-0.34). Although we saw considerable differences in the magnitude of response by COMPASS-HF randomization group (total data access for physicians vs. blocked clinician access), season, left ventricular ejection fraction, and obesity, these effects were not significantly different. Conclusions: These pilot study findings provide a potential mechanism for previous findings of increased risk of HF associated with ambient PM. However, because of the small number of subjects, a larger study is needed for confirmation.